Assessment of nutritional characteristics of conventional and non-conventional feedstuffs for small ruminants using physical, chemical and in vitro methods - Giger-Reverdin S.; Duvaux-Ponter C.; Sauvant D.; Rihani N.; Sos-Dahbi E.; Baraka A. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
The assessment of nutritional characteristics of conventional and non-conventional feedstuffs for small ruminants is of particular practical importance as these animals very often use local forages and by-products. Besides chemical assays, several easy-to-perform physical methods (bulk density, water holding capacity, initial pH, intrinsic buffering capacity) have been used for a set of 45 samples obtained from two different countries (France and Morocco) and covering a wide range of compositions. Short-term in vitro gas production was also measured. There were no differences between conventional and non-conventional feedstuffs for the relationships between the physical and chemical parameters. These relationships were poor, implying that the physical parameters might give additional information on feed characteristics. The proposed physical methods could be of interest to predict the fill value, and the in vitro gas method should estimate the potential acidogenicity of feedstuffs.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)